Rooftop Farm Soils for Sustainable Water and Nitrogen Management - Harada, Yoshiki; Whitlow, Thomas H.; Bassuk, Nina L.; Russell-Anelli, Jonathan (Frontiers in Sustainable Food Systems, 2020)
Rooftop farming intends to diversify options for enhancing sustainability of cities. From a policy perspective, vegetable production and stormwater management are among important goals of rooftop farming for bolstering public funding and policy support. However, crops with high value and market demand like salad greens often have high irrigation requirements, which risks increasing drainage output of water and nutrients. To date, no studies have compared various soil mixes intended for rooftop farms in terms of stormwater retention, yield and quality of drought-sensitive crops constrained by regional precipitation patterns. Here, we report the results of a 5-week greenhouse experiment with leaf lettuce comparing 5 soil mixes made of coconut coir, biochar, and animal manure compost, plus a commercial rooftop farm soil using expanded shale, using an irrigation rate mimicking average growing season precipitation for New York City, USA. Three soil mixes had good yield, with water retention rates ranging up to 100%, while levels of drainage nitrogen output were less than 13% of current levels at the Brooklyn Grange, an operational rooftop farm in NYC. This finding suggests that improved soil design could enhance sustainability of rooftop farming in terms of water and nutrient management. Further research is needed for adjustment of nitrogen mineralization rates, long-term amendment plan, locally available waste inventory for substituting coconut coir, and leachate and rainwater harvesting systems.